2022
DOI: 10.1002/ppul.26026
|View full text |Cite
|
Sign up to set email alerts
|

Video game‐based exercise in children and adolescents with non‐cystic fibrosis bronchiectasis: A randomized comparative study of aerobic and breathing exercises

Abstract: Background: Video game-based systems have been proposed to improve effectiveness and compliance with exercise training in children and adolescents with noncystic fibrosis bronchiectasis (NCFB). This study aimed to investigate the effects of aerobic and breathing video game-based exercises (VGE) on pulmonary function, respiratory and peripheral muscle strength, functional capacity, and balance in children and adolescents with NCFB. Method: Thirty-nine children and adolescents aged between 8 and 18 years with NC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Airway clearance in non‐CF bronchiectasis is an important aspect of disease management 32 . Ucgun et al 33 hypothesized that a video game‐based exercise (VGE) program would be a fun and effective way for children with non‐CF bronchiectasis to perform airway clearance. They conducted an eight‐week prospective cohort study in which they divided 39 children into three groups: chest physiotherapy (CP) alone, CP plus aerobic VGE program, or CP plus a breathing VGE program.…”
Section: Non‐cf Bronchiectasis and Pcdmentioning
confidence: 99%
See 1 more Smart Citation
“…Airway clearance in non‐CF bronchiectasis is an important aspect of disease management 32 . Ucgun et al 33 hypothesized that a video game‐based exercise (VGE) program would be a fun and effective way for children with non‐CF bronchiectasis to perform airway clearance. They conducted an eight‐week prospective cohort study in which they divided 39 children into three groups: chest physiotherapy (CP) alone, CP plus aerobic VGE program, or CP plus a breathing VGE program.…”
Section: Non‐cf Bronchiectasis and Pcdmentioning
confidence: 99%
“…Airway clearance in non-CF bronchiectasis is an important aspect of disease management. 32 Ucgun et al 33 A rare disorder of motile cilia, PCD presents with chronic rhinosinusitis, bronchitis, and sometimes laterality defects. 34 Diagnostic testing remains imperfect, as both genetic testing and evaluation of ciliary ultrastructure under electron microscopy each miss around 30% of cases.…”
Section: Non-cf Bronchiectasis and Pcdmentioning
confidence: 99%
“…In a study by Joo et al, VR breathing training (VRBT) was used for stroke patients, which reduced breathlessness and improved exercise performance and quality of life of the patients [ 7 ]. Another study states that VRBT improves the strength of respiratory muscle for patients with non-cystic fibrosis bronchiectasis [ 8 ]. Patients with neurological impairment to motor involvement show better outcomes with treatments such as biofeedback [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the treatment techniques take into account the patient’s interests and daily living activities, which is more helpful with VR treatment [ 9 - 11 ]. VRBT improves the strength of muscles of respiration, which is the alternative for respiratory muscle training in bronchiectasis patients [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, the health benefits resulting from therapeutic exercise have not been systematically investigated in children with bronchiectasis. A recent study involving 39 children and adolescents with non-CF bronchiectasis reported active video gaming to improve aerobic fitness and muscular strength; however, because exercise was combined with an extensive home-based physiotherapy program comprising ventilatory muscle training and postural drainage with percussion, the independent effects of exercise training on the fitness and respiratory outcomes could not be delineated ( 8 ). We have previously shown that children with bronchiectasis are insufficiently active for health benefit ( 9 ) and exhibit significant developmental delays in fundamental movement skill (FMS) proficiency ( 10 ).…”
Section: Introductionmentioning
confidence: 99%